2017
DOI: 10.1353/hpu.2017.0019
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Contraceptive Use among Women of Reproductive Age in Rural Districts of Burkina Faso

Abstract: Given the current low contraceptive use and corresponding high levels of unwanted pregnancies leading to induced abortions and poor maternal health outcomes among rural populations, a detailed understanding of the factors that limit contraceptive use is essential. Our study investigated household and health facility factors that influence contraceptive use decisions among rural women in rural Burkina Faso. We collected data on fertile non-pregnant women in 24 rural districts in 2014. Of 8,657 women, 1,098 used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
22
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 46 publications
7
22
2
Order By: Relevance
“…The study was done to determine the uptake and factors influencing the uptake of PPIUCD among the women delivering in a tertiary care hospital of Odisha, India. The study findings are contrary to a study by Wulifan et al [12] who found that optimal contraceptive use among women of reproductive age was higher in young…”
Section: Age As a Facilitatorcontrasting
confidence: 99%
See 3 more Smart Citations
“…The study was done to determine the uptake and factors influencing the uptake of PPIUCD among the women delivering in a tertiary care hospital of Odisha, India. The study findings are contrary to a study by Wulifan et al [12] who found that optimal contraceptive use among women of reproductive age was higher in young…”
Section: Age As a Facilitatorcontrasting
confidence: 99%
“…The least number were Catholics who do not advocate for artificial methods of contraception. The study findings agree to a study by Wulifan et al [12] who found that low contraceptive use among women of reproductive age was influenced by religious beliefs of the women. This was a study on factors associated with contraceptive use among women of reproductive age in rural district of Burkina Faso.…”
Section: Employment As a Facilitatorsupporting
confidence: 91%
See 2 more Smart Citations
“…The distance to a health facility is a problem because it is related to the indirect costs of transportation which are incurred when seeking modern contraceptives while these costs are not covered under any national health promotion scheme and thus, they constitute a burden for poor women. The association of distance and contraceptive use echoes earlier studies that indicate contraceptive use declines among women are five kilometers away from a health facility in Burkina Faso [47] and two kilometers away from a community-based health planning centers in the Upper East region of Ghana [48]. Further, the trend across regions suggests that in addition to the imbalanced distribution of resources, the region is relevant to understand the disparities in family planning services.…”
Section: Discussionsupporting
confidence: 70%